2015
DOI: 10.1016/j.proenv.2015.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders Analysis: Managing Coastal Policy Implementation in Rembang District

Abstract: Karimunjawa is one of archipelagoes in Indonesia, which is rich in natural resources. Although it has been a policy as a national park area, there are still severe environmental degradations. This study aims to analyze how sustainable development based on ecological, economic and social are implemented in Karimunjawa archipelago; and to analyze several alternative development policies in order to select the most appropriate policy that can be recommended to the government, considering that sustainability is ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Besides, some problems occurred in planning, implementation, monitoring and evaluating (M&E) were not as well as expected. Whereas, role of stakeholders gave important effect the implementation of environment conservation as Kismartini and Yusuf (2015) found that role of functionary policy management in coastal area in Rembang Regency both the main actor or supporter have strong effect in observing management of coastal area and coordinating with actors were running appropriate with the authority.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Besides, some problems occurred in planning, implementation, monitoring and evaluating (M&E) were not as well as expected. Whereas, role of stakeholders gave important effect the implementation of environment conservation as Kismartini and Yusuf (2015) found that role of functionary policy management in coastal area in Rembang Regency both the main actor or supporter have strong effect in observing management of coastal area and coordinating with actors were running appropriate with the authority.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Power is derived from 5 key sources: 1) relevant legal authority for decision-making and implementation, including rules and laws: 2) having up to date information to strive the interests of consumers; 3) having particular expertise in consumer protection based on not only the consumer law but also the consumer policy, planning and management; 4) take over the costs and resources to support the activities and 5) the ability to mobilize the masses to change the policy. Has Interest, which is interpreted as the degree on which stakeholders demand all the attention in the policy process (Kismartini & Yusuf, 2015). State Government: Ministry of Energy and Mineral Resource and Ministry of Environment, Regional Government Institution -Environmental Monitoring Agency, Local Government of Provinces and top-down administratives including tourism institutions, Law enforcer: police, military, civil investigator, Commission of Corruption Erradication, National Intelligence Organizations and Government Internal Auditors have the power to carry out, investigate and executing any violation related to water crimes.…”
Section: Table2 Illustration Of Stakeholder Analysis Represented In Relate To the Enforcement Of Water Law And Minimizing Water Conflict mentioning
confidence: 99%
“…To further enhance the investigation of coastal dynamics in Jayapura City, additional sources can be explored. These additional sources may include studies on the ecological impacts of land use change in coastal areas, assessments of vulnerability and resilience to climate change, analyses of policy implications for coastal management, and case studies of successful adaptation strategies in similar contexts [19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%